Possible conduction mechanisms in coconut-shell activated carbon - W. Yusoff, W. Mohamad Daud; Badri, M.; Hashim, Mansor (American Institute of Physics, 1990)
This work reports on the result of electrical conductivity measurements carried out on coconut-shell activated carbon. The results suggest that the charge carriers moved by variable-range hopping below 200 K, by hopping among localized energy states between 200 K and 385 K, and by percolation through energy states close to the mobility edge above 385 K. In the latter two conduction processes, significant additional frequency-dependent contributions to the conductivity were observed and are tentatively attributed to polarization of unremovable lignin and/or ionic impurities. These explanations are based on the present trends of the electrical transport theory for amorphous semiconductors.